PENYELIDIKAN OLEH KEPOLISIAN SEKTOR BUKIT RAYA KOTA PEKANBARU DALAM MENANGGULANGI TINDAK PIDANA PERJUDIAN SABUNG AYAM DI KECAMATAN BUKIT RAYA - Wira Tri Ananda; Erdianto '; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Gambling in Indonesia this is a matter that is quite disturbing people so that it is disputed. The number of gambling cases uncovered by law enforcement, it is a proof that gambling in Indonesia can not be eradicated in practice. One form of gambling that is rife in traditional societies is a cockfight gambling Law enforcement is the job of the Police of the Republic of Indonesia, can be mentioned as a police officer living law. Through the position that the police have the responsibility to secure and protect the public. The purpose of this thesis, namely: First, to know the police investigation Sector Bukit Raya Pekanbaru against the crime of gambling cockfights in the district of Bukit Raya Pekanbaru, Second, what are the obstacles in the investigation of the crime of gambling cockfights in the Police Sector Bukit Raya, Third To know the prevention of cockfight gambling in the jurisdiction of the Police Sector Bukit Raya.This research is a law research sosiologis.Penelitian Criminal Police was conducted in Bukit Raya, while the overall population and the sample is related to the overall problems examined in this penlitian. Source of data used is primary data, secondary data, and the data tertiary. Data collection techniques in this study were interviews and questionnaires and literature study and data analysis technique used is by a qualitative way.From the research results can be concluded that, First, Performance police investigator in the police Bukit Raya is not optimal and the investigation is only waiting for a report from the public so that the absence of public statements. Second, barriers investigations in combating the crime of cockfighting gambling, Bukit Raya police faced a number of obstacles, such as External Constraints: Operation ambush possibility of leaks beforehand, internal constraints are less synchronization of tasks between intelligence units and units reskrim in combating cockfight gambling. Third prevention efforts that have been done Bukit Raya sector police in tackling the crime of cockfighting gambling, there are three kinds of efforts to pre-emptive, preventive and repressive efforts. Suggestions Author, First Bukit Raya Police Sector should take decisive and thorough steps in the investigation of this case Second, law enforcement authorities in dealing with gambling case cockfighting to be more conscientious in his duties by involving the community. Third, always consistent in his actions both in terms of running the Pre-emptive, preventive and repressive. The police should be more active at the time of disseminationKeywords: Research-Police Bukit Raya-Gambling cockfighting